Patrol career interest and perceptions of barriers among African-American criminal justice students. Issue 3 (19th October 2018) - Rossler, Michael T.; Scheer, Charles; Suttmoeller, Michael J.
Abstract : Purpose: The purpose of this paper is to evaluate whether black and African-American criminal justice students perceive barriers to a police patrol career differently than white students, and whether the perceptions of these barriers impact desire to enter a police patrol career. Design/methodology/approach: The current inquiry uses a self-administered survey of over 630 undergraduate students in criminal justice classes across five public universities. Findings: Findings suggest that African-American students differ significantly from white students in perceived social disapproval of patrol careers, respect for police and perceptions of whether the police engage in racial profiling. These perceptions display a significant indirect relationship indicating lower patrol career interest for black and African-American students compared to all other races. Research limitations/implications: Research limitations of the current inquiry include the lack of a nationally representative sample, the use of four-year university students as a sample to represent the potential police patrol applicant pool, and the use of a survey instrument to gauge respondent beliefs about patrol careers as opposed to actions they would take in pursuit of a police career. Practical implications: Findings from the current inquiry indicate that departments may need to focus more on improving global perceptions of the police and discussing the nature of the career with recruit social support structures. Police recruiters should focus on techniques such as addressing social isolation experienced by the police rather than on decreasing standards for background checks or simply increasing awareness of police careers. Originality/value: The current inquiry is one of the first to explore perceptions of barriers to entering a patrol career among CJ students. It is also among the first to examine the impact these perceptions have on patrol career interest. The findings may also help criminal justice instructors more fully discuss these barriers with students of color.